2021
DOI: 10.3390/pr9091662
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Drying, Size Reduction, and Blanching in Sustainable Extraction of Phenolics from Olive Leaves

Abstract: It is now known that olive leaves contain a sizable portion of polyphenols and there is much research highlighting that these natural ingredients favorably exhibit bio-functional activities. In this regard, many studies have focused on the exploration of optimum conditions involved directly in the extraction process. These investigations, while being highly valuable, may somewhat cast a shadow over other contributing factors such as those involved in the preprocessing of leaves, including size reduction, dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…19 The obtained results here, regardless of the factor of particle size, concur with previous research that observed significant effects of adding olive leaves on the increment of aforementioned pigments in the final extracted oil. 20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The obtained results here, regardless of the factor of particle size, concur with previous research that observed significant effects of adding olive leaves on the increment of aforementioned pigments in the final extracted oil. 20…”
Section: Resultsmentioning
confidence: 99%
“…The choice of adding dry leaves rather than fresh ones was based on the extensive studies reviewed previously. 2,3…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of pre-treatment and processing methods may influence the reduction in extraction time, an increase in extraction yield, quality of the biological compounds, and reduction in input energy [ 28 ]. The drying of any biomass inhibits microbial growth [ 18 ], and it aids in the longer shelf life and transportation costs due to the weight and space of dry products [ 29 , 30 , 31 ].…”
Section: Pre-treatment and Processing Of Biomassmentioning
confidence: 99%
“…The drying of any biomass inhibits microbial growth [ 18 ], and it aids in the longer shelf life and transportation costs due to the weight and space of dry products [ 29 , 30 , 31 ]. Drying can affect the phytochemical components of the thermally sensitive components [ 29 , 32 , 33 , 34 ], and the process can also contribute to improved conservation of the bioactive compounds against oxidative [ 35 ] and enzymatic activities [ 36 ] and spoilage bacteria [ 30 , 37 , 38 ], enabling cellular destruction [ 28 , 30 , 35 ]. There are many different drying methods, e.g., thermal through natural convection (shade and open sun drying), forced convection (oven drying, solar drying, and heat pump drying), freeze-drying, greenhouse drying, microwave drying, and infrared drying [ 28 ].…”
Section: Pre-treatment and Processing Of Biomassmentioning
confidence: 99%